How do I write tan(2 sin^-1(x)) as an algebraic expression?

1 answer

Consider a right-angled triangle with hypotenuse = 1, and opposite = x

sinθ = opposite/hypotenuse = x/1
then by Pythagoras the adjacent side = √(1-x^2)
and cosθ = √(1-x^2)

sin^-1(x) is the angle θ so that sinθ = x
then tan(2 sin^-1 (x) )
= tan (2θ)
= sin 2θ / cos 2θ
= 2sinθcosθ/(cos^2 θ - sin^2 θ)
= 2x√(1-x^2) / (1-x^2 - x^2)
= 2x√(1-x^2) / (1- 2x^2)
Similar Questions
    1. answers icon 13 answers
  1. 1. Which is an example of an algebraic expression?A. 4(3 +8) B. 18^2 C. 3 - a D. 21 . 4 *** 2. Which is an algebraic expression
    1. answers icon 21 answers
  2. 1. Which is an example of an algebraic expression?A. 4(3+8) B. 18^2 C. 3 - * D. 21 x 4 2. Which is an algebraic expression for 5
    1. answers icon 9 answers
    1. answers icon 3 answers
more similar questions